The Influence of Character Building, Learning Environment and Self Efficacy on Students' Work Readiness - Partono, Partono; Aji, Yudisworo; Irdianto, Windra (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2020)
Students' readiness to work was considered essential for because the more interest that individuals have, in this case, are students; the higher their work readiness in their efforts to achieve the desired goals. This study aimed to determine the effects, both partially and simultaneously, of character-building variables, learning environment, and self-efficacy on work readiness. This research was descriptive quantitative research. The population in this study was the twelve grade students of Automotive Lightweight Vehicle Engineering at Public Vocational High School 1 Trenggalek with a total of 143 students, and the samples were 107 students that were chosen using the proportional random sampling technique. The instruments in this study were questionnaires and documentation. The analysis of research data used descriptive statistical analysis, multiple linear regression analysis, classic assumption test, which included normality test, multicollinearity test and heteroscedasticity test. The hypothesis testing included t-test and f-test, determination coefficient (R2) and significant contribution. Based on the data analysis, the results showed that there was partially and simultaneously significant influence of character building variables, learning environment and self-efficacy on work readiness of the twelve grade students of Automotive Lightweight Vehicle Engineering at Public Vocational High School 1 Trenggalek.